PENGARUH EKSTRAK DAUN SERAI (Cymbopogon citratus (DC.) Stapf) TERHADAP PERKEMBANGBIAKAN KUTU BERAS (Sitophilus oryzae L.) - Miftachur Rohma; Moh Mirza Nuryady; Sri Wahyuni (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[THE EFFECT OF LEMONGRASS (Cymbopogon citratus (DC.) Stapf) LEAVES EXTRACT ON RICE WEEVIL (Sitophilus oryzae L.) REPRODUCTION]. Rice weevil (Sitophilus oryzae) is the most destructive pest of rice. S. oryzae can be controlled with lemongrass (Cymbopogon citratus). C. citratus leaves extract can be used as pests control because it contains potential active compounds. This study aims to determine the effect of the several concentrations of C. citratus extract from fresh and dry leaves on S. oryzae reproduction. This study was used factorial RAL with two factors. The first factor was concentrations which were divided into 5%, 10%, 20%, as well as the positive control group (alfamethrin 1%) and the negative control group (aqua dest). The second factor was the use of C. citratus leaves which were divided into fresh and dry leaves. Parameters observed were the repellent of S. oryzae, the number of new adults, the damaged rice percentage, and the rice organoleptic. The rice organoleptic was conducted to observe color, texture, smell, and taste. The data were analyzed using a two-way ANOVA test. The best result has been found in the concentration of 20% from fresh C. citratus treatment with an average repellency of 68.50±14.45%, the number of new adults of 29±4.99, and the damaged rice percentage of 24.75±4.113%. The result of the organoleptic test with the highest average value was found in the concentration 5% from fresh C. citratus treatment. The results of the organoleptic test with Kruskal-Wallis showed that there were no significant differences in the color, texture, smell, and taste of rice. The conclusion of this study showed that C. citratus can be used effectively against S. oryzae.